Association between training volume and lower extremity overuse injuries in young female athletes: implications for early sports specialization - Sugimoto, D.; Jackson, S. S.; Howell, D. R.; Meehan III, W. P.; Stracciolini, A. (The Physician and Sportsmedicine, 2019)
Background: Recent studies indicated greater risk of overuse injuries among young female athletes than their male counterparts. However, few studies have focused on female athletes and the effect of single-sport participation on lower extremity overuse injuries.